Development of an experimental rotary magnetic refrigerator prototype. (August 2019) - Huang, B.; Lai, J.W.; Zeng, D.C.; Zheng, Z.G.; Harrison, B.; Oort, A.; van Dijk, N.H.; Brück, E.
Highlights: A magnetic refrigerator prototype with real-time controlled solenoid valves. Easy accessible regenerator design for testing materials in arbitrary geometry. Low-cost magnetic field source design for homogeneous field with sharp boundary. Maximum cooling power of 162.4 W is achieved with a low magnetic field of 0.875 T. Abstract: A rotary active magnetic regeneration refrigerator prototype named FAME Cooler was developed for studying the performance of different magnetocaloric materials in a realistic practical environment. The rotary magnetic field source generates an average magnetic field of 0.875 T within a volume of 0.71 l The regenerator is designed asymmetrically and holds in total 1.18 kg of gadolinium spheres for a first performance test. Combined with a real-time controlled programmable solenoid-valves system, different working parameters or thermodynamic cycles can be applied. In the performance test, while the temperature of system hot side was fixed at 295 K, under a utilization condition of 0.25, this prototype achieved a maximum zero-span cooling power of 162.4 W, and a zero-power temperature span of 11.6 K. Under a utilization condition of 0.15, a maximum COP of 1.85 was reached. These performance metrics are comparable with existing magnetic heat pump devices of the same scale.